Auditing social media : a governance and risk guide - Scott, Peter R. , 1964-; Jacka, J. Mike (Wiley, 2011)
This book provides auditors and risk managers with a primer on social media. It discusses what social media is, how it is being used as a tool within corporations, and how it should be monitored